Jordanian Speech Pathology Students’ Beliefs and Attitudes Toward People Who Stutter (PWS) - Alamawi, Samar; Al Khamaiseh, Zaidan; Qanawati, Laila; A. Zabalawi, Dima (Journal of Ecohumanism, 2024)
This research aims to better understand how speech pathology students in Jordan perceive and interact with individuals who stutter (PWS). During their time as undergraduate clinical trainees, it seeks to shed light on how these aspiring professionals view stuttering and associated speech disorders. Also, in order to determine how much of an effect experience has on students’ viewpoints, the study plans to compare those of juniors and seniors. It measured these sentiments using a modified version of the CATS and the POSHA-S scales, which stand for the Public Opinion Survey of Human Attributes-Stuttering. The online poll was filled out by 110 students from Al-Ahliyya Amman University, split evenly between first- and second-year students as well as third- and fourth-years. Experts verified the Arabic version of the 30-question survey, which inquired about demographics, stuttering knowledge, stuttering impact perceptions, PWS competence, and general opinions. There was no statistically significant difference in the beliefs on the causes of stuttering between the two groups, but the results showed that senior students had substantially more knowledge about stuttering than juniors. From an attitude perspective, both groups showed neutral to positive feelings towards PWS, with the seniors showing a little more positivity. The disparity between the sexes in terms of optimistic outlooks was also not statistically significant, but female students did exhibit a general trend toward more optimistic views and attitudes. The survey found that students, particularly seniors, have a typically positive attitude and are becoming more confident when it comes to coping with PWS.The research shows that higher levels of education are associated with more positive attitudes and understanding of stuttering. As compared to juniors, seniors had somewhat more positive attitudes and greater knowledge, indicating that higher education enhances professional efficacy and empathy. Students’ opinions ranged from neutral to positive on the whole, with girls showing more optimism than boys. The results highlight the need of teaching students about communication impairments in a positive light while also providing them with the technical skills necessary for the field of speech pathology.